The Ethical Dilemma of Software Piracy: An Inquiry from an Islamic Perspective - Hewa Majeed Zangana; Imad Fakhri Al-Shaikhli; Yuliana Isma Graha (Universitas Raharja, 2013)
Software piracy in the Muslim countries is a prevailing issue. It has been estimated based on BSA by 2009 that more than 90% of software in Yemen is pirated, followed by Libya 88%, Indonesia 86%, and Iraq 85%. UAE has the lowest rate for software piracy, which is 36%. While in the Middle East area, the piracy rate is around 59% with total commercial value of 2,887 Million. Furthermore, the software piracy remains a critical issue in Asia Pacific, with the region accounting for the highest dollar losses in the world from the use of unlicensed software. The survey of software piracy around the world, which is collaboration between the Business Software Alliance (BSA) and IDC, indicates that software piracy on personal computers in the Asia Pacific region in November 2009 was 61 percent, worth 15,000 million U.S. dollars (BSA, 2009; IDC Global PC). The purpose of this study is to understand the software piracy from Islamic perspective and finding the recommendations, solutions ofthis problem to deter software piracy as much as possible. Focusing on the Islamic rule, evidence and argument relating to copyright infringement especially software piracy in the Islamic world; additionally, the effect of software piracy